THE DIFFERENCE OF ENGLISH VOCABULARY MASTERY BETWEEN BOYS AND GIRLS - mary ika; ayu muassari; Audi Yundayani (Journal of English Language and Literature (JELL), 2018)
The objective of the research was to find out English vocabulary mastery between boys and girls, including words size in production. This was a descriptive qualitative research. The data was taken from students’ writing product. The data analysis was conducted through collecting, reducing and displaying. The research finding showed that, 1) the girls are able to produce more words than the boys; and 2) the girls have more vocabularies amount than boys.